In Situ Surface‐Directed Assembly of 2D Metal Nanoplatelets for Drug‐Free Treatment of Antibiotic‐Resistant Bacteria. Issue 19 (1st September 2022) - Fathi, Parinaz; Roslend, Ayman; Alafeef, Maha; Moitra, Parikshit; Dighe, Ketan; Esch, Mandy B.; Pan, Dipanjan
Abstract: The development of antibiotic resistance among bacterial strains is a major global public health concern. To address this, drug‐free antibacterial approaches are needed. Copper surfaces have long been known for their antibacterial properties. In this work, a one‐step surface modification technique is used to assemble 2D copper chloride nanoplatelets directly onto copper surfaces such as copper tape, transmission electron microscopy (TEM) grids, electrodes, and granules. The nanoplatelets are formed using copper ions from the copper surfaces, enabling their direct assembly onto these surfaces in a one‐step process that does not require separate nanoparticle synthesis. The synthesis of the nanoplatelets is confirmed with TEM, scanning electron microscopy, energy dispersive spectroscopy (EDS), X‐ray diffraction (XRD), and Fourier transform infrared spectroscopy (FT‐IR). Antibacterial properties of the Cu nanoplatelets are demonstrated in multidrug‐resistant (MDR) Escherichia coli, MDR Acinetobacter baumannii, MDR Staphylococcus aureus, E. coli, and Streptococcus mutans . Nanoplatelets lead to a marked improvement in antibacterial properties compared to the copper surfaces alone, affecting bacterial cell morphology, preventing bacterial cell division, reducing their viability, damaging bacterial DNA, and altering protein expression. This work presents a robust method to directly assemble copper nanoplatelets onto any copper surface to imbue it with improved antibacterial properties. Abstract : A surface modification technique is used for the direct self‐assembly of 2D copper nanoplatelets onto copper surfaces. These nanoplatelets exhibit antibacterial properties against multi‐drug‐resistant bacteria.